Evaluation of the effects of Locust Bean Gum application on loess solidification and vegetation growth - Jinlong Zhang; Yanwei Hou; Tao Jiang; Kekuo Yuan (Discover Applied Sciences)
Abstract An attempt was made to apply LBG in loess solidification. The impacts of applying LBG at various concentrations (0%, 0.5%, 1%, 1.5%, and 2%) and employing distinct curing periods (1, 2, 4, and 7 days) on the unconfined compressive strength, tensile strength, and disintegration characteristics were evaluated. The results demonstrated that an increase in the LBG content is correlated with an increase in both the uniaxial compressive strength and the tensile strength. Nevertheless, the rate of strength enhancement diminished progressively with higher LBG concentrations. A concentration of 2% is recommended for practical applications. The uniaxial compressive and tensile strengths of the LBG-modified loess samples were more than 1.5 times greater than those of the untreated loess samples. Moreover, the peak uniaxial compressive strength of the enhanced samples reached 426.8 kPa after seven days of curing. The improved soil also demonstrated excellent anti-disintegration performance, as evidenced by weight gain due to water absorption over the experimental period. Notably, no disintegration occurred during water immersion. The grass growth characteristic test results indicated that LBG-modified loess supported more vigorous growth. These results provide crucial reference data for ecological soil reinforcement and low-carbon construction.